Addressing gender-based constraints of smallholder women farmers in mid-hills of Nepal - Basnet, Salu; Maskey, Gyanu; Acharya, Sushant (Southasia Institute of Advanced Studies, 2023)
Impacts of climate change, COVID-19, and feminization of agriculture have exacerbated uncertainties in agriculture in Nepal’s mid-hills and increased women’s burden. In such a context, the research in two districts of Nepal aimed at addressing the gender-based constraints (GBCs) to empower women’s engagement in higher nodes of the value chain for vegetables in Arghakhanchi and for legumes in Ramechhap. This paper discusses: a) the research findings on gender-based constraints along the sociocultural, economic, policy, technological and environmental domains; b) the reflective approaches of the interventions, based on identified GBCs, and how these interventions were helpful in addressing the GBCs. The research adopted a qualitative approach, including key informant interviews, focused group discussions, photo stories, policies review, deliberative forums, and a policy expert meeting, and used N-VIVO for the data analysis. To address the GBCs identified as time poverty, limited mobility to access market, low bargaining power, limited access to finance, and financial and digital literacy, in Ramechhap the interventions focused on strengthening the farmer cooperative and branding and marketing of the legumes. While in Arghakhanchi, a process of coproduction—continuous engagement and dialogue—led to the re-opening of the local market (haat-bazaar). Further, Women Champions’ identification as role models and GESI and local planning orientations have motivated other women and helped to develop action plans to address their GBCs to further the agenda of economic empowerment. The insights and reflections have broader relevance to other municipalities in addressing GBCs through key interventions and GESI-responsive policies and programs.